Process Evolution of Women as Senior Executives and Influential Business Leaders in Peru: a Grounded Theory Approach - Portugal Manrique, Rocío Margot (Pontificia Universidad Católica del Perú, 2021)
The purpose of this qualitative, grounded theory study was to understand why so few women have achieved CEO positions or similar high positions in large companies in Peru. Although a small number of women, about 12% in the executive committees and 17% on corporate boards, have achieved high or executive positions worldwide (McKinsey, 2019), those women who have achieved top senior leadership position are a phenomenon that deserves to be studied in order to understand the process involved. In this study, conducted using a grounded theory approach, 18 executives with the position of CEO, board member or senior partner in a large company in Peru were interviewed in depth. The interviews were semi-structured, and the data was analyzed using the constant comparative method suggested by Strauss & Corbin (1990) and supported by MAXQDA software for qualitative data analysis. The results identified a complex process in the career ascent of these women executives. Fourteen dimensions - endogenous, exogenous and interconnected theoretical categories - emerged in the process. These findings were elevated into a substantive theory called the process of the evolution of women executives into influential business leaders. This study’s findings form a basis that could be used to build upon until a firm theory is developed, which could help understand this phenomenon from within to help managers, and particularly women, to implement policies that give women equal opportunity to men to reach the upper echelon of company management structures.
Keywords: Mujeres ejecutivas--Liderazgo--Perú; Mujeres en los negocios--Perú; http://purl.org/pe-repo/ocde/ford#5.02.04